2018
DOI: 10.1556/030.65.2018.007
|View full text |Cite
|
Sign up to set email alerts
|

First report of Acanthamoeba genotype T8 human keratitis

Abstract: Acanthamoeba has a worldwide distribution in the environment and it is capable of causing a painful sight-threatening disease of the cornea designated as Acanthamoeba keratitis (AK). Nowadays, the cases of AK have surged all over the world along with its disease burden due to increasing use of contact lenses used not only for optical correction but also for cosmetic purposes. In our present work, epithelial abrasion of a 27-year-old female soft contact lens wearer with keratitis was examined. Genotype identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
1
15
0
2
Order By: Relevance
“…The molecular analysis conducted in this study confirmed, in our series of patients, the T4 genotype to be the most frequent cause of AK. In addition, one isolate was T8 genotype and was first associated with AK [26]. These results are consistent with previous findings indicating that T4 is worldwide predominant in AK [27,28].…”
Section: Discussionsupporting
confidence: 92%
“…The molecular analysis conducted in this study confirmed, in our series of patients, the T4 genotype to be the most frequent cause of AK. In addition, one isolate was T8 genotype and was first associated with AK [26]. These results are consistent with previous findings indicating that T4 is worldwide predominant in AK [27,28].…”
Section: Discussionsupporting
confidence: 92%
“…have been identified, some of which are pathogenic and others non-pathogenic. Identification of genotypes in each environment and geographical region and determination of its dominant genotype is very valuable ( Niyyati et al, 2009 ; Niyyati et al, 2015 ; Hajialilo et al, 2016 ; Niyyati and Rezaeian, 2015 ; Badirzadeh et al, 2011 ; Mataji Bandpei, 2016 ; Orosz et al, 2018 ). The results of the studies on environmental samples have shown that T4 genotype is highly dispersed in the environment, these samples can be considered as important risk factors for AK.…”
Section: Discussionmentioning
confidence: 99%
“…These must have a difference of at least 5% in order to be considered different sequences. 2 To date, 25 species 27 and 20 different genotypes of Acanthamoeba (T1-T20) 28,46,[49][50][51][52] have been recognised.…”
Section: Genotyping Of Acanthamoebamentioning
confidence: 99%